Design and Synthesis of Novel Breast Cancer Therapeutic Drug Candidates Based upon the Hydrophobic Feedback Approach of Antiestrogens - Kiminori Ohta; Asako Kaise; Fumi Taguchi; Sayaka Aoto; Takumi Ogawa; Yasuyuki Endo (Molecules, 2019)
Based upon hydrophobic feedback approaches, we designed and synthesized novel sulfur-containing ERα modulators (4 and 5) as breast cancer therapeutic drug candidates. The tetrahydrothiepine derivative 5a showed the highest binding affinity toward ERα because of its high hydrophobicity, and it acted as an agonist toward MCF-7 cell proliferation. The corresponding alkylamino derivative 5d maintained high binding affinity to ERα and potently inhibited MCF-7 cell proliferation (IC50: 0.09 μM). Docking simulation studies of compound 5d with the ERα BD revealed that the large hydrophobic moiety of compound 5d fit well into the hydrophobic pocket of the ERα LBD and that the sulfur atom of compound 5d formed a sulfur−π interaction with the amino acid residue His524 of the ERα LBD. These interactions play important roles for the binding affinity of compound 5d to the ERα LBD.